Reduksi Kemiskinan dengan Mengoptimalkan Digitalisasi Ekonomi Maritim di Provinsi Sulawesi Tenggara - Ilyas; Tajuddin; Syamsir Nur; Caesar Muslim; Isalman (Journal of Economics Development Issues, 2023)
This study aims to determine the steps taken to reduce poverty through optimizing the digital-based maritime economy. This research method uses a quantitative approach. The data used is secondary data. Data analysis was done by descriptive analysis. The results of this study indicate that there are several steps taken by the Southeast Sulawesi Government to encourage the optimization of digitalization in the maritime sector including building synergy and collaboration between local governments and relevant ministries; development of social media and film-based tourism; optimizing the role of local governments; providing quality human resources in the digital field and increasing digital infrastructure development.